Research Note—Why Following Friends Can Hurt You: An Exploratory Investigation of the Effects of Envy on Social Networking Sites among College-Age Users - Krasnova, Hanna; Widjaja, Thomas; Buxmann, Peter; Wenninger, Helena; Benbasat, Izak (Information Systems Research, 2015)
Research findings on how participation in social networking sites (SNSs) affects users’ subjective well-being are equivocal. Some studies suggest a positive impact of SNSs on users’ life satisfaction and mood, whereas others report undesirable consequences such as depressive symptoms and anxiety. However, whereas the factors behind the positive effects have received significant scholarly attention, little is known about the mechanisms that underlie the unfavorable consequences. To fill this gap, this study uses social comparison theory and the responses of 1,193 college-age Facebook users to investigate the role of envy in the SNS context as a potential contributor to those undesirable outcomes. Arising in response to social information consumption, envy is shown to be associated with reduced cognitive and affective well-being as well as increased reactive self-enhancement. These preliminary findings contribute to the growing body of information systems research investigating the dysfunctional consequences of information technology adoption in general and social media participation in particular.